Identification of cultivable heat tolerant wheat genotypes suitable for Patuakhali district in Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
Fifteen wheat genotypes namely Agrani, Prodip, Bijoy, CB 69, Sourav, Sufi, BAW 1064, Gourab, Kanchan Shatabdi, CB 30, Sonora, CB 24, CB34, and Protiva were sown under optimum (Nov. 30) and late (Dec. 30) sowing times to evaluate their performances at high temperature depending on cell membrane thermostability and some morpho-physiological characters. Based on cell membrane thermostability test four genotypes showed the longest heat killing time and were separated as heat tolerant (HT). Four genotypes showed the shortest heat killing time and were separated as heat sensitive (HS). The remaining seven genotypes required time in between those two were separated as intermediate heat tolerant (IHT) genotypes. Lower contribution of photosynthate stem reserves (PSR) to grain in HT genotypes finally contributed to its less affected 1000-grain weight as well as yield. These results suggest that greater cell membrane thermostability supported the minimal changes in some physiological characters of HT ganotypes which ultimately increased the wheat yield under short winter warmer condition. Keywords: Membrane thermostability; Wheat genotype DOI: 10.3329/jbau.v7i2.4729 J. Bangladesh Agril. Univ. 7(2): 241-246, 2009